Computational design methods and technologies applications in CAD, CAM, and CAE education - Gu, Ning; Wan, Xiangyuan (Information Science Reference, 2012)
"This book explores state-of-the-art developments in computational design methods and their impact on contemporary design education, offering case studies, empirical research findings, pedagogical theories, and reflections" - Provided by publisher
Includes bibliographical references
Keywords: Datenverarbeitung; Erziehung; Computer-aided engineering; Computer-aided design; CAD/CAM systems; Education / Data processing; Aufsatzsammlung